Establishing systems & processes for classroom observation of teaching in EAP - Bell, Douglas (N/A, 2021)
Classroom observation can boast a long and venerable history in English Language Teaching and is now an accepted feature of professional life. Such observation is either seen as being evaluative in nature, in which case it is typically linked with appraisal systems and carried out by a line manager, or it may be viewed more developmentally, in which case it is more commonly conducted on a peer-to-peer basis. While the mechanisms for both types of classroom observation in General ELT contexts are now quite well established, the same cannot always be said of observations in EAP, where approaches may be more idiosyncratic and based on the preferences of individual institutions. In the specific case of evaluative classroom observation, a further consideration is whether the observation should be focussing on the same kinds of features as those found in General ELT contexts or looking for evidence of something else. This reflective paper charts the evolution, establishment and delivery of one such EAP-specific approach to evaluative classroom observation, which was conducted at the University of Nottingham Ningbo China (UNNC) between 2009 and 2015.